Working towards Usable Forms on the World Wide Web: Optimizing Date Entry Input Fields - Javier A. Bargas-Avila; Olivia Brenzikofer; Alexandre N. Tuch; Sandra P. Roth; Klaus Opwis (Advances in Human-Computer Interaction)
When an interactive form in the world wide web requires users to fill in exact dates, this can be implemented in several ways. This paper discusses an empirical online study with n = 172 participants which compared six different versions to design input fields for date entries. The results revealed that using a drop-down menu is best when format errors must be avoided, whereas using only one input field and placing the format requirements left or inside the text box led to faster completion time and higher user satisfaction.